Implementasi Sistem Kontrol Pakan Burung Puyuh Berbasis Mikrokontroler Dan Internet Of Things (Iot) - Tijaniyah tijaniyah; Muhammad Firdaus; Muhammad Fikri Maula (Universitas Islam Lamongan, 2021)
The quail egg business is a type of business that is now popular with the community. Good quail care is also an important thing for the community to pay attention to, including feeding that should not be late, because if it is too late to feed, the quail can no longer produce eggs. Quail is capable of producing 10 to 20 eggs in one egg. The majority of people raise about 300 to 500 quails. Automatic feeding is one of the important things in this study. The time of feeding is morning, afternoon, evening and night. Researchers also use a microcontroller, nodemcu and the Internet of Things (IOT). The function of the IOT is as a remote control media on off feeding time and control the opening and closing of the door to the quail feed.